Improving Teacher Performance Through Total Quality Management and Academic Supervision - Zahara Tussoleha Rony; Khairil Anwar; Muhammad Nur; Suyitno Suyitno; Upik Khoirul Abidin (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2024)
This research is interesting to conduct to analyze the variables that influence teacher performance, including the variables of total quality management and academic supervision. If we look at the media, which focuses on the development of teacher performance, the performance of teachers in Indonesia is still in the spotlight. The initial goal of the study is to determine how total quality management affects teacher performance. The second goal is to determine how academic supervision affects teacher performance. The third goal is to determine how both total quality management and academic supervision affect performance at the same time. This kind of study uses surveys as a quantitative research methodology. 88 persons in all were chosen by the census procedure to be respondents. The information utilized was gathered using a questionnaire that was distributed directly to respondents.